Ultralight and Resilient Bicontinuous Si3N4/SiC Nanowire Network for Tunable and Highly Efficient Electromagnetic Wave Absorption in Extreme Conditions. Issue 35 (26th October 2022) - Cai, Zhixin; Su, Lei; Niu, Min; Wang, Lei; Ni, Zhentao; Wang, Hongjie; Peng, Kang; Zhuang, Lei
Abstract: Developing tunable and highly efficient electromagnetic wave (EMW) absorbers with low density is crucial for the development of wireless telecommunications devices in extreme conditions. SiC ceramic has received much attention because of its dielectric tenability, low density, and chemical stability. However, the present SiC‐based materials usually show limited EMW absorbing performance than they are expected. Herein, an ultralight and resilient bicontinuous Si3 N4 /SiC network (8 mg cm −3 ) composed of EMW‐transparent Si3 N4 microbelts and EMW‐absorption SiC nanowires is designed and prepared to achieve improved impedance matching and EMW attenuation capacity. The optimized bicontinuous network exhibits a broad effective absorption bandwidth of 8.62 GHz and a strong RLmin of −52.31 dB. Furthermore, the resulting bicontinuous Si3 N4 /SiC network, with thickness of 6 mm, shows a tunable absorption bandwidth ranging from 5.36 to 18 GHz by resilient action. It also exhibits excellent thermal stability (up to 1000 °C), thermal shock resistance (from −196 to 900 °C), and thermal insulation performance (32 Mw m −1 K −1 ), enabling it to be an ideal candidate for EMW absorption in extreme environments. Abstract : An ultralight and resilient bicontinuous Si3 N4 /SiC network (8 mg cm −3 ) composed of electromagnetic wave (EMW)‐transparent Si3 N4 microbelts and EMW‐absorption SiC nanowires is designed and prepared to achieve improved impedance matching and EMW attenuation capacity. The network shows excellent thermal stable and resilient compressibility up to 50% strain, during which the absorption band can be tuned from 5.36 to 18 GHz.